Degradation behavior of dimethyl phthalate in an anaerobic/anoxic/oxic system. (15th December 2016) - Zhang, Tao; Huang, Zehua; Chen, Xiaohong; Huang, Mingzhi; Ruan, Jujun
Abstract: Dimethyl phthalate (DMP) as one of the most important and extensively used Phthalic acid esters (PAEs) is known to likely cause dysfunctions of the endocrine systems, liver, and nervous systems of animals. In this paper, the degradation and behavior of DMP were investigated in a laboratory scale anaerobic/anoxic/oxic (AAO) treatment system. In addition, a degradation model including biodegradation and sorption was formulated so as to evaluate the fate of DMP in the treatment system, and a mass balance model was designed to determine kinetic parameters of the removal model. The study indicated that the optimal operation condition of HRT and SRT for DMP and nutrients removal were 18 h and 15 d respectively, and the degradation rates of anaerobic, anoxic and aerobic zones for DMP were 13.4%, 13.0% and 67.7%, respectively. Under the optimal conditions, the degraded DMP was 73.8%, the released DMP in the effluent was 5.8%, the accumulated DMP was 19.3%, and the remained DMP in the waste sludge was 1.1%. Moreover, the degradation process of DMP by acclimated activated sludge was in accordance with the first-order kinetics equation. The model can be used for accurately modeling the degradation and behavior of DMP in the AAO system. Highlights: The fate of dimethyl phthalate (DMP) was investigated in a bioprocess system. A removal kinetic model including sorption and biodegradation was formulated. Kinetic parameters were evaluated using a mass balance model. The degradation rate of DMP can be described by a first-order kinetics equation.